2020
DOI: 10.3390/pr8030319
|View full text |Cite
|
Sign up to set email alerts
|

Apple Pomace as a Functional and Healthy Ingredient in Food Products: A Review

Abstract: Apple pomace is a major by-product obtained during apple juice processing. Several million metric tons of apple pomace are estimated to be generated worldwide every year. However, the recovery rate of this by-product is low. Pomace is commonly disposed and thrown away as a waste, which results in environmental problems and even public health hazards. As a by-product of the apple juice processing industries, pomace contains plenty of different varieties of nutritionally important compounds, such as carbohydrate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
134
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 170 publications
(139 citation statements)
references
References 85 publications
4
134
1
Order By: Relevance
“…Considering the content of APF in yogurt with the best sensorial properties and texture, the regular consumption of a portion of 100 mL per day can be recommended for better body weight control and diabetes prevention. All the presented results justify the use of APF-fortified probiotic yogurts in human nutrition and significantly contribute to general knowledge about the implementation of APF in the production of dairy products, the shortcomings of which are highlighted in [42]. However, quality changes in APF-fortified probiotic yogurts during storage should be examined in order to unambiguously confirm the distinct values of this novel product.…”
Section: Resultsmentioning
confidence: 52%
“…Considering the content of APF in yogurt with the best sensorial properties and texture, the regular consumption of a portion of 100 mL per day can be recommended for better body weight control and diabetes prevention. All the presented results justify the use of APF-fortified probiotic yogurts in human nutrition and significantly contribute to general knowledge about the implementation of APF in the production of dairy products, the shortcomings of which are highlighted in [42]. However, quality changes in APF-fortified probiotic yogurts during storage should be examined in order to unambiguously confirm the distinct values of this novel product.…”
Section: Resultsmentioning
confidence: 52%
“…Apple pomace is acidic and piled together will quickly ferment and deteriorate, which wastes resources and pollutes the environment. Using biological fermentation technology and suitable combination of microbial composite strains, the nutritional value of the peel and pomace after biological fermentation is greatly improved and has advantages in food products [ 82 ]. In addition to the significantly increased crude protein content, the product also contains beneficial micro-ecological factors, which has become an excellent green biological feed with dual characteristics of protein feed and micro-ecological preparation.…”
Section: Apple-derived Products and Prospectsmentioning
confidence: 99%
“…After harsh juice processing, the experimental group still presented 37.2 Ā± 1.3 mg GAE/g dry powder polyphenols, and 18.5 Ā± 0.8 mg RE/g dry powder flavonoids, which indicated that aronia processing by-products are an effective resource for antioxidant materials. Various studies have also reported that phenolic compounds remain in by-products after juice processing [9,[39][40][41]. However, the polyphenols and flavonoids extracted from the bioelastomer were found to be lower than the powder.…”
Section: Antioxidant Activity Of Aronia Powders and Bioelastomersmentioning
confidence: 99%
“…The fruit juice processing industry has become one of the largest markets in the agro-industrial sector [8]. Juice processing by-products are usually buried directly in the soil, which causes serious environmental pollution [9]. However, these by-products still contain bioactive compounds such as tannins, flavonoids, flavanols, vitamins, essential minerals, fatty acids, volatiles, and pigments, which can be utilized as natural bioactive compounds [10].…”
Section: Introductionmentioning
confidence: 99%